the clinical significance of luteal therapy in the stimulate cycle following the transfer of superovulated embryos - Albarzanhi, Mundhir R.; Allow, ahmed K.; Balafair, Amer S.; Taiyeb, Ahmed M.; Al-Anssari, saada (Journal of the Faculty of Medicine Baghdad, 2006)
Background: